1995
DOI: 10.1136/hrt.74.4.449
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in participants and non-participants of a multifactorial prevention study of cardiovascular diseases: a 28 year follow up of the Helsinki Businessmen Study.

Abstract: Objective-To investigate pretrial risk factors and long term mortality in participants and nonparticipants of a multifactorial primary prevention trial. Design-A prospective study among 3313 initially healthy businessmen. During the 1960s (1964 onwards), 3490 healthy male business executives born between 1919 and 1934 participated in voluntary health checks at the Institute of Occupational Health in Helsinki. From that period cardiovascular disease (CVD) risk factors were available in 3313 men. In the beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 32 publications
5
22
0
Order By: Relevance
“…Some studies (not using mail questionnaires) have compared mortality between participants and non-participants in community-based surveys with screening examinations which aimed mainly at clarifying risk factors for cardiovascular disease [11][12][13][14] Most studies showed that non-participants had higher total mortality than participants 11-14) Our results are in agreement with these studies and suggest that non-respondents tend to be less healthy than respondents. Because more non-respondents than respondents may have been ill at the beginning of the survey, we recalculated age-adjusted rate ratios for all causes of death between respondents and non-respondents, excluding data from the first two years of the study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Some studies (not using mail questionnaires) have compared mortality between participants and non-participants in community-based surveys with screening examinations which aimed mainly at clarifying risk factors for cardiovascular disease [11][12][13][14] Most studies showed that non-participants had higher total mortality than participants 11-14) Our results are in agreement with these studies and suggest that non-respondents tend to be less healthy than respondents. Because more non-respondents than respondents may have been ill at the beginning of the survey, we recalculated age-adjusted rate ratios for all causes of death between respondents and non-respondents, excluding data from the first two years of the study.…”
Section: Discussionsupporting
confidence: 83%
“…The above mentioned community-based surveys with screening examinations had similar findings [12][13][14]. In particular, our study showed that the difference in mortality between non-respondents and respondents was much greater for cardiovascular disease than for cancer.…”
Section: Discussionsupporting
confidence: 70%
“…However, many studies have shown that non-respondents are different from respondents [1,[3][4][5][6][7][8][9][10]. When respondents and non-responders differ considerably, the 70% response rate is not enough to ensure accurate and precise populations estimates and response rate of 90% or higher may be needed [18].…”
Section: Response Ratementioning
confidence: 98%
“…When the unit and item non-response are completely random, estimators of prevalence or association among variables based on respondents are unbiased but the precision is reduced [2]. Several studies have shown, however, that non-respondents differ from respondents in relation to socio-economic status and health profile [3][4][5][6][7][8][9][10]. These differences between respondents and non-respondents may bias estimators obtained from respondents' data especially if the response rate is low and/or these differences are large.…”
Section: Introductionmentioning
confidence: 99%
“…However, so far not many randomized intervention studies have been published on the prevention of cardiovascular disease (CVD) at the worksite (9)(10)(11). It is also still unclear which method of screening for cardiovascular risk factors should be recommended in this setting, as traditional screening programs (eg, with blood sampling on a broad basis) are often costly, time-consuming, and of limited value (12).…”
mentioning
confidence: 99%